Is there a point? Teachers' perceptions of a policy incentivizing the study of advanced mathematics. Issue 6 (1st November 2020) - Prendergast, Mark; O'Meara, Niamh; Treacy, Paraic
ABSTRACT: A growing body of international research has highlighted the importance of students studying mathematics at an advanced level. In Ireland, the subject has been assigned a special status with the introduction of an education policy called the Bonus Points Initiative (BPI) in 2012. Students are now awarded an extra 25 points in their final State examination results if they achieve ≥40% in advanced/Higher Level (HL) mathematics. This incentive has had a noticeable impact and the numbers opting for HL mathematics in the final State examination have increased from 15.8% in 2011 to 32.9% in 2019. While this is undoubtedly a positive development, there has been little research about any knock-on effects regarding the teaching and learning of the subject. This article examines HL mathematics teachers' ( n = 266) perceptions of the BPI. The findings reveal many mixed opinions with more teachers (46%) agreeing with the initiative than disagreeing (27%), recognizing advantages such as increasing numbers and rewarding students. However, issues perceived by teachers such as questionable student motivation and the negative impact on the pace of lessons appear to be key reasons for a majority of teachers recommending a review (56%) or discontinuation (23%) of the initiative.